Micro-Textural Controls on Magma Rheology and Vulcanian Explosion Cyclicity - Bain, Amelia A.; Kendrick, Jackie E.; Lamur, Anthony; Lavallée, Yan; Calder, Eliza S.; Cortés, Joaquín A.; Cortés, Gloria Patricia; Gómez Martinez, Diego; Torres, Roberto A. (Frontiers in Earth Science, 2021)
Understanding the relationship between degassing, crystallization processes and eruption style is a central goal in volcanology, in particular how these processes modulate the magnitude and timing of cyclical Vulcanian explosions in intermediate magmas. We conducted high-temperature (940°C) uniaxial compression experiments on eight samples of high crystallinity andesite with variable plagioclase microlite populations from the 2004–2010 Vulcanian explosions of Galeras volcano, Colombia. Experiments were conducted at different strain rates to measure the rate-dependence of apparent viscosities and assess the dominant deformation processes associated with shear. Variations in plagioclase micro-textures are associated with apparent viscosities spanning over one order of magnitude for a given strain rate. Samples with low numbers of large prismatic microlites behaved consistently with published rheological laws for crystalline dome samples, and displayed extensive micro-cracking. Samples with high numbers of small tabular microlites showed a lower apparent viscosity and were less shear-thinning. The data suggest a spectrum of rheological behavior controlled by concurrent variations in microlite number, size and shape. We use previously published micro-textural data for time-constrained samples to model the apparent viscosity of magma erupted during the 2004–2010 sequence of Vulcanian explosions and compare these results with observed SO2 fluxes. We propose that variations in magma decompression rate, which are known to produce systematic textural differences in the plagioclase microlite cargo, govern differences in magma rheology in the shallow conduit. These rheological differences are likely to affect the rate at which magma densifies as a result of outgassing, leading to magmatic plugs with a range of porosities and permeabilities. The existence of magmatic plugs with variable physical properties has important implications for the development of critical overpressure driving Vulcanian explosions, and thus for hazard assessment during volcanic crises. We suggest a new conceptual model to explain eruption style at andesitic volcanoes based on micro-textural and rheological differences between ‘plug-forming’ and ‘dome-forming’ magma. We advance that existing rheological laws describing the behavior of andesitic magma based on experiments on dome rocks are inappropriate for modelling large Vulcanian explosions (~10^6 m3), as the magma involved in these eruptions lacks the characteristics required to form exogenous lava domes.